1962
DOI: 10.1021/jf60121a006
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Sources, Metal Ammonium Phosphates as Fertilizers

Abstract: Deficiency in corn causes a shortening of the internodes of corn and a severe stunting.A typical zinc-deficient plant is shown in Figure 9. When the deficiency is severe, many corn plants will die in the seedling stage, with those recovering exhibiting several different colorations and symptoms ranging from a lack of green color in the upper leaves to interveinal striping in the upper leaves. Severe zinc deficiency in corn is known as "white bud."Zinc deficiencies are corrected by soil applications of zinc sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 5 publications
(8 reference statements)
3
78
0
2
Order By: Relevance
“…The literature studied had three field scale experiments. These showed increases in available P after struvite application (Bridger et al, 1962;Cabeza Perez et al, 2009;DLV, 2008), but did not show differences as clearly as pot experiments. None of the studies in Table 4 indicated that struvite exceeded any regulatory limits or reduced crop growth significantly.…”
Section: P Availability To Plants and The Behavior Of Struvite In Thementioning
confidence: 90%
See 3 more Smart Citations
“…The literature studied had three field scale experiments. These showed increases in available P after struvite application (Bridger et al, 1962;Cabeza Perez et al, 2009;DLV, 2008), but did not show differences as clearly as pot experiments. None of the studies in Table 4 indicated that struvite exceeded any regulatory limits or reduced crop growth significantly.…”
Section: P Availability To Plants and The Behavior Of Struvite In Thementioning
confidence: 90%
“…Metal contamination was investigated and posed a risk from dirty feedstock in some cases (Abma et al, 2009;Escher et al, 2006;Goto, 1998;Li & Zhao, 2003;Matsumiya et al, 2000;Schuiling & Andrade, 1999;Ueno & Fujii, 2001;Weinfurtner et al, 2009). One study investigated plant growth in pure struvite (Bridger et al, 1962) and another with very high doses (Li & Zhao, 2003), and still found no problems with plant growth! Fig.…”
Section: P Availability To Plants and The Behavior Of Struvite In Thementioning
confidence: 99%
See 2 more Smart Citations
“…The good agronomic properties of struvite are known since the middle of 20 th century (Bridger et al, 1961). The use of technology to separate nutrients from wastewater, sewage sludge and its ashes and after These are some innovative strategies to improve the sustainability of P fertilisation contributing to close the cycle of P use.…”
Section: Fertilisers Manufactured From Organic Wastesmentioning
confidence: 99%